Molecular Detection of Canine Babesiosis in and Around Bhubaneswar, India - Panda, Charchika; Dehuri, Manaswini; Panda, Mitra R.; Sahoo, Lakshman K.; Mohanty, Bijayendranath (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Canine babesiosis, a hemolytic protozoan disease, represents an important veterinary problem caused primarily by large and smallforms of piroplasms of Babesia spp. A molecular-based survey on the overall occurrence of natural Babesia infection in stray (n=98 )and pet dogs (n=100) from Bhubaneswar and nearby areas using PCR technique targeting 18s RNA gene fragment along with geneticsequence analysis was carried out. A total of 38 (pet:22, stray:16) samples (19.19%) were found positive for babesiosis based on theamplification of 450 bp amplicon region of the gene, while 4 samples (0.02%) showed co-infection with Hepatozoon canis. The sequencedPCR products were submitted to NCBI, and on BLAST analysis, the isolates with accession no KT246303, KT246306, KT246307 showingsimilarity with Babesia vogeli, while KT246305 was identical to B.gibsoni isolates and KT246304 was identical to Hepatozoon canis. Thisis the first report on the molecular diagnosis of canine babesiosis in the state.
Keywords: Babesia vogeli; Babesia gibsoni; India; Molecular detection